Effect of organic fertilizer and formulated feed in pond culture of the freshwater prawn, Macrobrachium rosenbergii (de Man): pond productivity - Maclean, M.H.; Brown, J.H.; Ang, K.J.; Jauncey, K. (Wiley-Blackwell Publishing, 1994)
Abstract. The application of different combinations and levels of pellet formulated feed and chicken manure to ponds stocked with Macrobrachium rosenbergii (de Man) did not result in any significant differences in water quality, sediment chemistry, or benthic macroinvertebrate populations. Water chemistry data indicated that all ponds were eutrophic. Chlorophyll was strongly correlated with total nitrogen, but not with total phosphorus, suggesting that nitrogen limited algal biomass. There was evidence that added organic matter was rapidly decomposed and mineralized. The sediments appeared to act alternately as sources and sinks of nutrients, although there was least variation in sediment nutrient levels in the treatment which received manure only. Applied pelleted feed was directly consumed by the prawns. In the absence of pelleted feeds, macrobenthos appeared to limit prawn growth after 1 month of culture. Simple nutrient mass-balance equations indicated that the losses of nitrogen, phosphorus and carbon from the treatments receiving feed were not dissimilar to previously reported values in finfish culture.